MATLAB for engineers - Moore, Holly (ESource--the Prentice Hall engineering source, 2007)
With a hands-on approach and focus on problem solving, this introduction to the powerful MATLAB computing language is designed for students with only a basic college algebra background. Numerous examples are drawn from a range of engineering disciplines, demonstrating MATLAB's applications to a broad variety of problems.